2016
DOI: 10.1097/aln.0000000000001084
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal Fluid Oxaliplatin Contributes to the Acute Pain Induced by Systemic Administration of Oxaliplatin

Abstract: Background Systemic administration of oxaliplatin has no effect on the tumors in the central nervous system (CNS) due to the limited concentration of oxaliplatin in the cerebrospinal fluid (CSF), while it was clinically reported that oxaliplatin can induce acute encephalopathy. Currently, the impairment of neuronal functions in the CNS after systemic administration of oxaliplatin remains uninvestigated. Methods The von Frey t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
38
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 43 publications
3
38
0
Order By: Relevance
“…33) Recently, evidence has emerged that the expression of TNF-α and IL-1β is increased in varieties of neuropathic pain models such as chronic sciatic nerve injury and oxaliplatin-induced peripheral neuropathic pain. [34][35][36] Peripheral or intrathecal application of TNF-α and IL-1β antagonists could effectively inhibit the pain. 37) Curcumin, as a phytochemical isolated from turmeric, has been investigated with promising anti-carcinogenic activity by in vitro and pre-clinical researches, and studies suggested that curcumin is able to target a range of tumorigenic pathways.…”
Section: Discussionmentioning
confidence: 99%
“…33) Recently, evidence has emerged that the expression of TNF-α and IL-1β is increased in varieties of neuropathic pain models such as chronic sciatic nerve injury and oxaliplatin-induced peripheral neuropathic pain. [34][35][36] Peripheral or intrathecal application of TNF-α and IL-1β antagonists could effectively inhibit the pain. 37) Curcumin, as a phytochemical isolated from turmeric, has been investigated with promising anti-carcinogenic activity by in vitro and pre-clinical researches, and studies suggested that curcumin is able to target a range of tumorigenic pathways.…”
Section: Discussionmentioning
confidence: 99%
“…4,5 While CIN was described initially as a predominantly reversible condition that produced its effects within the peripheral nervous system, a growing body of evidence suggests that it persists long into survivorship 6 and that the neurotoxic effects can occur within the central nervous system. 79 Therefore, in this paper the abbreviation CIN was used instead of CIPN to describe this condition. Of note, in 2014, CIN was added to the National Comprehensive Cancer Center (NCCN) Clinical Practice Guideline for Survivorship 2,10 and the American Society of Clinical Oncology published a guideline on the prevention and management of CIN in cancer survivors.…”
Section: Introductionmentioning
confidence: 99%
“… 6 , 7 Recently, CX3CL1 has been identified to mediate painful responses in chemotherapy drug-induced pain models. 8 10 Upregulation of CX3CL1 in spinal dorsal horn contributed to oxaliplatin-induced acute pain. 8 In addition, activation of CX3CL1/CX3CR1 signaling in DRG plays a pivotal role in paclitaxel-induced painful peripheral neuropathy.…”
Section: Introductionmentioning
confidence: 99%